Redesign of the Agribusiness Market Area in Ngablak District, Magelang Regency with a Behavioral Architecture Approach - Muhammad Syahrul Rifki; Majora Nuansa Al-Ghin; Andi Purnomo (Canopy: Journal of Architecture, 2025)
Indonesia is an archipelagic country with abundant natural resources both in terms of biological and non-biological, one of the dominant wealth of Indonesia is the agricultural sector, this is supported by the land in Indonesia which is dominated by loose soil with high fertility levels. Therefore, agriculture has been very closely associated with the indigenous people of Indonesia, even if seen from History, agriculture has become a way of life or lifestyle for the community. Ngablak District in Magelang Regency is one of the areas in question, with its geographical location on three mountain slopes namely Mount Andong, Mount Telomoyo, and Mount Merbabu, making the land in the Ngablak area very fertile, this is what makes the community very dependent on the agricultural sector. Therefore, the need for a space that is able to act as an intermediary for agricultural actors in trading and what has developed in Indonesia is the Agribusiness Market. The Agribusiness Market is a market related to the agricultural business or other fields that support it, the Planning of the Agribusiness Market in Ngablak District, Magelang Regency aims to create facilities for the community as an agricultural trade space and the like. With a behavioral architecture approach, this building is designed to respond to the habits of the community or users.